Percutaneous Mitral Repair with the MitraClip System in Patients with Mild‐to‐Moderate and Severe Heart Failure: A Single‐Centre Experience. Issue 2 (April 2014) - Bozdag‐Turan, Ilkay; Paranskaya, Liliya; Birkemeyer, Ralf; Turan, R. Gökmen; Kische, Stephan; Akin, Ibrahim; Ortak, Jasmin; Stoeckicht, Yannik; Schubert, Jochen; Westphal, Bernd; Nienaber, Christoph A.; Ince, Hüseyin
Summary Aims Edge‐to‐edge repair of mitral regurgitation (MR) with the MitraClip® (MC) system is increasingly applied in advanced heart failure. Our objective was to compare outcomes in patients with mild‐to‐moderate and severe systolic heart failure. Methods and results Between February 2010 and July 2012, 121 patients with MR of at least grade 3+ and a mean EuroSCORE II of 10.6% underwent MC implantation. Thirty‐nine had a left ventricular ejection fraction (LVEF) of ≤30% (group A) and 82 of >30% (group B). Procedural success was comparable in both groups (100% vs. 95.2%) with multiple (>2) clip implantation in 34% and 25% of patients, respectively. At 12 months, absolute reduction in MR grade (2.3 vs. 2.2) and relative reduction in mitral valve orifice area (48% vs. 42%) were also comparable. New York Heart Association class had improved independent from baseline LVEF (P < 0.001). In‐hospital mortality was low in both groups (2.6% vs. 2.4%), but there was a strong trend for higher 12‐month mortality in group A (34% vs. 18%, P = 0.05) with no significant difference in the overall rate of major adverse cerebrovascular and cardiac events (36.8% vs. 28.9%, P = 0.38). On multivariate analysis, MR grade after repair was the strongest predictor of mortality (OR 2.121, 95% CI 1.095–4.109), whereas systolic impairment was no independent predictor. Conclusions Percutaneous mitral valve repair led to comparable symptomatic improvement in patients with mild‐to‐moderately or severely reduced LV function. LV‐EF < 30% was not an independent predictor of short‐term mortality, which was mainly governed by residual MR after repair.